Convolution Conditions for Some Subclasses of Meromorphic Bounded Functions of Complex Order: Mohamed Kamal Aouf, Adela Mostafa, Hanaa Zayed - Team, Support (Thai Journal of Mathematics, 2016)
Making use of the operator H_q,s(α₁) for functions of the form: f(z)=(1/z)+∑_k=1^∞a_kz^k-1 , which are analytic in the punctured unit disc U^∗=z:z∈ℂ and 0<|z|<1=U{0, we introduce two subclasses of meromorphic functions of complex order and investigate convolution properties, coefficient estimates and containment properties for these subclasses.